A dimensão subjetiva do processo participativo no planejamento da cidade: o caso do Plano Diretor Participativo de Jundiaí-SP - Polo, Daniel Rossin (2018)
Based on the conceptions of Socio-Historical Psychology, the research aims to characterize aspects of the subjective dimension of the participatory process of a municipal urban planning policy, accessed through the identification and analysis of the meanings present in different areas of the process. The research takes as its object the particularity of the Participative Master Plan of Jundiaí-SP, developed from 2014 and approved as a municipal law in 2016, specifically in relation to the processes of social participation understood as part of the mechanisms that seek to guarantee the right to city, as recommended by the City Statute. The empirical research was developed from two main procedures: a) reading and analysis of the content of the documents of the public policy, which presented and discussed the social participation models referenced and its execution; and b) individual interviews with four participants who composed the work of the Master Plan, all of whom were elected representatives of civil society. The analysis sought to discuss the aspects identified from three articulated contexts: political, procedural and singularities. What is perceived in the analysis is that the participatory process of urban politics was characterized by providing a contradictory subjective experience to the subjects. This means that, while it was based on democratic guidelines for urban planning, it pointed to the social function of the city as a precept and opened up to public participation, enabling innovative experiences, it also had limiting characteristics in its methodological strategies and, in a certain way, conservative strategies, such as reducing the issue of democratic participation to procedural aspects, non-explicitness and limits produced inequality in the representation of participants and maintaining liberal and elitist aspects of character in their speeches and positions. The advances and limitations that characterize the subjective dimension of the participatory process with a view to the production of a radically democratic policy are then considered, with the expectation that the case study will collaborate to broaden the discussions and practices of social participation in planning urban